Rethinking Catholic Religious Education Pedagogy Through Experiential Learning - Renniel Jayson Jacinto Rosales (Universal Journal of Educational Research)
Teaching the faith is challenging for educators, and applying different pedagogies is the last resort whenever one pedagogy fails to achieve the goal. This paper attempts to conceptualize a pedagogy by rethinking Catholic Religious Education (CRE) pedagogy through experiential learning. Through the different literature on pedagogy, the most influential Experiential Learning Theory of David Kolb emerged as the most fitted pedagogy for CRE. By focusing on the problems experienced in teaching CRE, merging theology and religious education, the principles of the pedagogy of faith (integration, inculturation, and community-building), and the essential components of faith (doctrine, morals, and worship), are seen as essential factors to be considered. The factors are appropriated separately to show each factor's overarching themes in the seamless experiential learning cycle of Kolb. Learning begins with experience and ends with new experiences strengthened by CRE's contents along the experiential learning process.